2008
DOI: 10.1007/s00259-008-0837-7
|View full text |Cite
|
Sign up to set email alerts
|

99mTc-interleukin-2 scintigraphy in normal subjects and in patients with autoimmune thyroid diseases: a feasibility study

Abstract: Purpose Radiolabelled interleukin-2 is a radiopharmaceutical used for the study of chronic inflammatory processes. 123 I-labelled interleukin-2 has successfully been used in a large number of patients affected by several immunemediated diseases. 123I, however, is expensive and not readily available. We have, therefore, developed a method for labelling interleukin-2 with 99m Tc to high specific activity based on the use of an N 3 S bifunctional chelating agent. In this paper, we describe the results obtained wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Succinimidyl-6-hydrazinopyridine-3-carboxylate (HYNIC-NHS) was conjugated to the commercially obtained IL2 as previously described [ 9 10 ]. Briefly, HYNIC-IL2 (100 μg) was incubated with tricine, 99m TcO - (370–740 MBq) and SnCl 2 for 10 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Succinimidyl-6-hydrazinopyridine-3-carboxylate (HYNIC-NHS) was conjugated to the commercially obtained IL2 as previously described [ 9 10 ]. Briefly, HYNIC-IL2 (100 μg) was incubated with tricine, 99m TcO - (370–740 MBq) and SnCl 2 for 10 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Due to concerns about potential adverse effects on the thyroid from a radioactive iodine based radiopharmaceutical, the investigators next employed a 99mTechnicium labeled interleukin-2 ( 99m Tc-IL2). We have demonstrated that this approach was able to visualize lymphocyte infiltration in the bowel (Crohn's disease) as well as in the thyroid (autoimmune thyroiditis) [ 7 9 ]. Next, we examined 21 early stage melanoma primary skin lesions prior to surgical resection with 99m Tc-IL2 imaging for the presence of TIL and corresponding 99m Tc-IL2 uptake by histologic evaluation of the surgical specimen.…”
Section: Introductionmentioning
confidence: 99%
“…Another study in asymptomatic Sjogren syndrome patients, salivary gland scintigraphy by 99m Tc-IL-2, showed clear pathological uptake in patients with biopsy-proven infiltrated glands [118].…”
Section: Examples Of the Use Of Radiolabeled Anti-tnfa Mabs In Chronimentioning
confidence: 98%
“…Studies using radiolabelled IL2 started in the 1980s and first radioisotopes used were 125 I and 35 S for in vitro and animal studies [134,135,136]. Radiolabelled IL2 was extensively studied in animal models and patients with diabetes [137,138,139,140], in order to research T lymphocyte infiltrates in rats’ renal allografts [141], in Crohn’s and coeliac disease patients [142,143], in other autoimmune disorders [144,145,146] and for imaging of vulnerable atherosclerotic plaques [147,148].…”
Section: Imaging Immunological Network In Cancermentioning
confidence: 99%